Original papersBleeding complications after percutaneous coronary interventions in patients treated with abciximab in relation to dose of clopidogrel - Kaźmierski, Maciej; Wieczorek, Piotr; Ochała, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2009)
Background: Administration of potent and fast-acting medications inhibiting platelet adhesion and aggregation is crucial to improve outcomes of percutaneus interventions. Aim: To compare the incidence of bleeding complications in patients treated with abciximab and different doses of clopidogrel. Additonal aim of the study was to compare the decrease of hemoglobin concentration. Methods: Medical records of patients who underwent invasive procedure between 2003 and 2006 were retrospectively analyzed. Patients treated with abciximab in standard dose and 75 mg or 300 mg of clopidogrel as the concomitant therapy were included. Exclusion criteria included: myocardial infarction caused by in-stent thrombosis, previous treatment with thienopyridine, participation in clinical trial with medication influencing the coagulation cascade, application of IIb/IIIa receptor inhibitor other than abciximab, lack of data in electronic records. For the purpose of the analysis of changes in the haemoglobin concentration patients who underwent surgical procedure were exluded. Results: Study group consisted of 324 patients, of whom 165 received 75 mg of clopidogrel and 159 received 300 mg of clopidogrel. Following complications were registered: haematoma of the arterial access site (diagnosis based on ultrasonography – organized hematoma exceeding 3 cm in diameter), pseudoaneurysm, retroperitoneal haematoma, gastrointestinal bleeding, haematuria. These complications was present in 6.7% patients who received 75 mg of clopidogrel and 11.9% patients who received 300 mg of clopidogrel (p = 0.1). Haemoglobin concentration decreased by 1.35 (0.6-2.2) g/dl in 75 mg group and by 1.8 (0.9-2.6) g/dl in 300 mg group (p = 0.046), respectively. Conclusions: Administration of 300 mg of clopidogrel together with abciximab is not significantly related to a higher frequency of bleeding complications, but it is related to a higher decrease of haemoglobin concentration in comparison to administration of 75 mg of clopidogrel. Special awareness concerning bleeding complications is needed when applying aggressive antiplatelet therapy.